PENGARUH FAKTOR FAKTOR MOTIVASI TERHADAP PRESTASI KERJA AGEN PELAYANAN ASURANSI JIWA PT.PRUDENTIAL DI SURABAYA - Ika Kharismawati (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2016)
This study was designed using a combination of descriptive and explanatory research. A descriptive study is used to illustrate the motivational factors and the performance of personnel service agency PT Prudential Branch Surabaya variables studied were:1) the independent variables, including: physiological needs, security needs, social needs, esteem needs and self-actualization, needs; 2) the dependent variable is the performance of the service agent This type of research that is used to describe the effect of physiological needs, security needs, social needs, esteem needs and self-actualization needs on the performance of the service agent. The analysis used is multiple linear regression analysis. The analysis showed that:a) physiological Needs, security needs, social needs, and the needs of self-esteem has a positive influence significantly on the performance operatiomal workers; b )the need for self-actualization has a non significant effect on the performance of operational worker; c) physiological needs to have a dominant influence on the performance of a service agency other independent variables; d) the study recommends that the physiological and safety needs require more advanced.